Nekateri pogledi na boj proti dopingu slovenskih športnikov in trenerjev - Kajtna, Tanja (Šport (Ljubljana), 2020)
Although doping is as old as sport, the phrase "fight against doping" gained its true meaning only upon the establishment of the World Anti-Doping Agency (WADA) in 1999. In Slovenia, this area is covered by the Slovenian Anti-Doping Organisation (SLOADO) which, through its education and testing programmes as well as a number of other activities, strives for clean sport. It is not only important how the WADA operates, but also what athletes' and coaches' perceptions of sport and WADA are. That is why we conducted a study, involving 448 participants (292 elite athletes and 156 coaches of elite athletes), where a survey questionnaire was used to investigate their attitude to sport and their opinion about its development. They were asked to state where they get information about doping and what their attitude to the Slovenian Anti-Doping Agency is. We compared these aspects between athletes and coaches, between male and female athletes, between athletes with medals from major championships and those less successful, as well as between athletes of team and individual sports. We reported some differences, namely athletes, more than their coaches, think that earning money and attaining fame is important; this is of particular importance to male athletes and to less successful athletes. Views on the development of sport differ between team and individual sports, and the main source of information about doping that our participants use is the SLOADO website. Coaches and athletes in individual sports would like the penalties for violations of anti-doping rules to be stricter.
Keywords: attitude to sport; coaches; doping; elite athletes; mnenjske raziskave; odnos do športa; opinion research; Slovenian Anti-Doping Organisation; Slovenska antidoping organizacija; šport; trenerji; vrhunski športniki